KAJIAN KINERJA PERSIMPANGAN TIDAK BERSINYAL (STUDI KASUS : PERSIMPANGAN TIGA GADUT, JALAN RAYA INDARUNG – BANDAR BUAT, KOTA PADANG) - Prayitno, Eko; Veronika, Veronika (Rang Teknik Journal, 2019)
The highway is one of the infrastructure for the smooth traffic. One part of the road that are considered necessary to be analyzed and evaluated is an intersection. Three Gadut intersection is non signalized intersection. The traffic flow is quite dense, and lack of discipline of road user factors competing space to pass the crossing, resulting in congestion is very influential on traffic conditions at peak hours in the morning, afternoon and evening. Prior to conducting the survey, the first to do is survey the condition of the intersection that includes geometric characteristics and traffic volume. From the analysis of environmental data, side friction factor to the junction of three Gadut is the criteria being. Rated capacity (C) the smallest is 3706.3 smp/hour, the degree of saturation of 1.1 smp/hour. This value is over the limit permitted values manually indonesian road capacity of 0.8 to 0.9 (1.1> 0.9), it is concluded that the traffic flow is the crossroads of three Gadut saturated traffic flow. The queue probability value between 128.8% - 157.4% with a total delay largest average 11.57 seconds/smp. It is concluded that the chances of a queue at the intersection of three Gadut very large, so it could cause congestion.